The Role of The Media in Promoting Eco-Tourism in Luang Prabang City - Lattananongsy, Sengthavy; Lounbandit, Douangchan; Thoummavong, Toulaphone; Sengpachith, Somphong (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This study attempts to investigate the satisfaction of Luang Prabang citizen on the role of communication media for promoting eco-tourism in Luang Prabang. the research instrument of this study was a set of questionnaires under 4 categories: Orientational gratifications; Social gratifications; Para-orientational gratifications and Para- Social gratifications. The sample groups of the current study were 385 people who are living in Laung Prabang with 242 females and 143 males, the statistics model applied for the data was SPSS, mean, and percentile and standard deviation were calculated. The results exhibited that the satisfaction of Luang Prabang citizen on Orientational gratifications was the first rang with M= 4.00, S.D = 0.991 or equal 80.07% of responses, followed up by Para- Social gratifications with M=3.78 or 78.56%; SD=1.054, the third rang of satisfaction on about Social gratifications with M=3.69, or 78.86%; S.D=0.976, while Para-orientational gratifications was the fourth rang of satisfaction with M= 3.50 or 70.05%; S.D= 1.16. On average the satisfaction of Luang Prabang citizen on the role of communication media for promoting eco-tourism in Luang Prabang was in high level.